Embracing the Future: Evaluating the Strategic Impact of Digital Supply Chain Integration on Business Performance (Journal of Asian Development Studies, 2023)
The main focus of this study is to elucidate the transformative influence of digital supply chains on business operations, performance, and strategy, emphasizing the benefits, challenges, and pivotal considerations accompanying the assimilation of digital technologies in supply chain processes. The research employs stratified random sampling across various industries with a structured survey questionnaire. The collected data was analyzed using regression analysis to establish relationships. Digital supply chains offer a substantial competitive advantage by improving operational efficiency customer satisfaction, and fostering innovation. However, continuous collaboration, supplier alignment, advanced operating models, organizational flexibility, and technological competencies are paramount for successful Implementation. Despite the advantages, challenges related to cybersecurity, data privacy, and resistance to change persist. For businesses looking to transition into digital supply chain models, this research provides a foundational understanding, highlighting the benefits, necessary considerations, and potential pitfalls. The study also underscores the importance of agility, collaboration, and technology competence in ensuring a successful transition.